Manufacturing culture : the institutional geography of industrial practice - Gertler, Meric S. (Oxford geographical and environmental studies., 2004)
Why are firms in some regions or nations so successful at adopting particular new production technologies and work practices, while those in other places are not? What role do culturally defined characteristics, traits, and attitudes play in determining the degree of success in this process? Moreover, to what extent can such successful practices be replicated or 'manufactured' in other less fortunate locations? These questions constitute the central issues of concern for this. book. - ;Recent years have seen a lively debate over the role of tacit knowledge and interactive learning in privilegi.